Pengaruh Media Tanam Terhadap Pertumbuhan dan Hasil Microgreen Mustard (Brassica juncea L.) - Theresa Dwi Kurnia; Isvan Fajar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of growing media on the growth, yield, and quality of mustard microgreens, as well as to determine the best growing media for cultivating mustard microgreens. The study was conducted from March to April 2024. This study was conducted in a greenhouse located at the Science Techno Park, Faculty of Agriculture and Business, UKSW Salatiga, Central Java, at an altitude of 1050 meters above sea level. This study was designed using a randomized block design (RBD) with 5 treatments and repeated 5 times. The growing media treatments consisted of A1 = soil, A2 = sponge, A3 = rockwool, A4 = rice husk charcoal, and A5 = cocopeat. The parameters observed included plant height, number of leaves, dry weight of plants, chlorophyll content, and vitamin C. The data from the study were analyzed using ANOVA at a significance level of 5% and further tested with the BNJ test at 5%. The results showed that rice husk charcoal and cocopeat media had a significant effect on plant height, while soil media had a significant effect on microgreen dry weight. The quality of microgreens based on chlorophyll and vitamin C content is not affected by the growing medium used. The conclusion of this study is that the use of rice husk charcoal and cocopeat as growing media for mustard microgreens cultivation can produce the best results and quality.